Organizing pneumonia following treatment with pembrolizumab for metastatic malignant melanoma – A case report. (2017) - Kuint, R.; Lotem, M.; Neuman, T.; Bekker-Milovanov, E.; Abutbul, A.; Laxer, U.; Berkman, N.; Fridlender, Z.G.
Abstract: Pembrolizumab is a monoclonal antibody against the programmed cell death 1 (PD-1) receptor, and is widely used for the treatment of various malignancies, most commonly malignant melanoma. Here we report the first documented and pathology proven case of Organizing Pneumonia complicating treatment with Pembrolizumab. This was a man who presented with a dense lung consolidation four months following treatment with Pembrolizumab. A thorough microbiological workup was negative and his findings did not improve with broad spectrum anti-microbial treatment. Transbronchial biopsy revealed organizing pneumonia, and treatment with cortico-steroids resulted in complete resolution of clinical and radiological disease. This report highlights the importance of recognizing immune related adverse events, specifically pulmonary inflammation, in patients receiving treatment with novel immune-modulating agents.